PEMBINAAN ORANG TUA UNTUK PENDIDIKAN KARAKTER ANAK DI ERA DIGITAL: PROGRAM PKM STT HKBP DI HKBP GARU VIII, MEDAN - Riris Johanna Siagian (Jurnal Abdi Insani, 2025)
The role of parents is very important and strategic in shaping children's character, especially in the digital era which is marked by rapid and fundamental changes in various aspects of life. This study aims to explore the understanding and challenges faced by parents in character formation, provide information to help parents comprehend their duties and responsibilities, encourage them to give full attention and affection to their children, and formulate the church’s role in strengthening support for Christian families. The Community Service Program (PkM) of HKBP Theological Seminary was conducted at HKBP Garu VIII, Ress. Sola Gratia, Amplas, Medan, with the topic “The Role of Parents in Shaping Children’s Character in the Digital Era.” The activity was attended by students of the Master of Theology Program at HKBP Theological Seminary and 32 informants consisting of church ministers and congregants. The research employed a qualitative method through Focus Group Discussion (FGD). The discussion revealed several findings: parents have limited understanding of their children’s way of thinking; they spend little time communicating with their children; they acknowledge having limited digital literacy; children are often busy with their own activities and prefer socializing with peers; and there is a general expectation that the church should give greater attention to children’s ministry. This study concludes that the church needs to provide teachings that strengthen the Christian calling and responsibility of parents in educating their children; design programs and spaces conducive to implementing character formation models such as family worship and outdoor children’s services accompanied by parents; and offer continuous mentoring by utilizing digital media.